Serum osteoprotegerin as an early marker of chronic kidney disease in hypertensive patients - Khaled A Elhefnawy; Ezzat M Mohamed; Athar M Abou Yousef; Abeer A Fikry; Hala M Allam (SpringerOpen, 2019)
Background Serum osteoprotegerin (OPG) is a marker of cardiovascular disease. The deterioration of renal function in diabetic patients could be predicted by OPG concentrations, and it was suggested that OPG could be used as a risk marker for chronic kidney disease (CKD) in patients with hypertension. Objective The aim was to investigate the role of serum OPG as an early marker of CKD in hypertensive patients. Patients and methods A total of 144 hypertensive patients were included and classified into two main groups: group I, which included 72 hypertensive patients without CKD [estimated glomerular filtration rate (eGFR) ≥60 ml/min/1.73 m2], and group II, which included 72 hypertensive patients with CKD (eGFR<60 ml/min/1.73 m2). All participants of the study were subjected to detail clinical examination and investigations including complete blood count, fasting and random blood glucose, glycosylated hemoglobin, urine analysis, serum creatinine, liver function tests, eGFR, and serum OPG assays. Results Serum OPG levels were significantly higher in hypertensive group with CKD than in hypertensive group without CKD. A significant positive correlation was found between OPG and diastolic blood pressure, duration of hypertension, serum creatinine, and albumin creatinine ratio, whereas there is a negative correlation between OPG and both weight and eGFR. The best cutoff value of serum OPG in prediction of CKD among hypertensive patients is greater than 1.9 ng/ml with sensitivity of 100% and specificity of 100%. Conclusion Serum OPG can serve as an early marker for CKD in hypertensive patients.